Innovation system formation in international development cooperation: The role of intermediaries in urban sanitation. (19th February 2020) - van Welie, Mara J; Boon, Wouter P C; Truffer, Bernhard
Abstract: The transformation of urban basic service sectors towards more sustainability is one of the 'grand challenges' for public policy, globally. A particular urgent problem is the provision of sanitation in cities in low-income countries. The globally dominant centralised sewerage approach has proven incapable to reach many of the urban poor. Recently, an increasing number of actors in international development cooperation has started to develop alternative safely managed non-grid approaches. We approach their efforts as an emerging 'global innovation system' and investigate how its development can be supported by systemic intermediaries. We analyse the activities of the 'Sustainable Sanitation Alliance', an international network that coordinates activities in the sanitation sector and thereby supports this innovation system. The findings show how demand ing it is to fulfil an intermediary role in a global innovation system, because of the need to consider system processes at different scales, in each phase of system building.